Agrowisata Kebun Jeruk Hijau Manis dan Strategi Pengembangannya - Sasmita Siregar; Khairunnisa Rangkuti; Enda Gemilang Prandini (JASc (Journal of Agribusiness Sciences), 2022)
This study aims to determine the characteristics of tourists, identify internal and external factors, and analyze development strategies that can be applied to Sweet Green Orange Garden Agrotourism in Pematang Kuing Village, Sei Suka District, Batu Bara Regency. Data analysis was carried out by means of descriptive analysis and SWOT analysis. The results showed that the internal factors that influence the development of agro-tourism are strength factors, including panorama, entrance ticket prices, facilities, and supervision, weakness factors are business location far from the city center, promotion that is not optimal, capital, and poor road access. not too good, the opportunity factor consists of the taste of tourists visiting back to nature tourist sites, increased visits on weekends, technological developments, employee capabilities, and cooperation with other parties, while the threat factor is tourists who tend to visit new tourist sites, the emergence of other agro-tourism, as well as the high level of competition; The alternative strategy obtained through the results of the SWOT matrix analysis consists of six alternative strategies to develop Sweet Green Orange Garden Agrotourism in Pematang Kuing Village.